Determination of the synergistic anti-influenza effect of Huangqin Su tablet and Oseltamivir and investigation of mechanism of the tablet based on gut microbiota and network pharmacology - Xuran Cui; Xibao Liu; Feng Wang; Kun Lou; Junping Hong; Hequn Bai; Rongchu Chen; Yang Yang; Qingquan Liu (BMC, 2023)
Abstract Huangqin Su (HQS) tablet is mainly composed of baicalein which has been evaluated for its ability to inhibit influenza. The present study aimed to investigate the effect of HQS and oseltamivir phosphate (OS) (single or combination therapy) on influenza-induced acute pneumonia in male and female ICR mice. The regulatory effect of HQS on gut microbiota was also studied by using 16 s rDNA sequencing, and the targets and mechanisms of HQS against influenza were comprehensively analyzed by network pharmacology. Pharmacodynamic results, including lung index and pathological changes, showed that HQS exhibited significant anti-influenza efficacy and could improve the efficacy of low-dose OS (P < 0.05 and P < 0.01, respectively). The results of 16 s rDNA sequencing revealed that HQS modulated the gut microbiota and remarkably enriched the abundance of Lactobacillus. The findings of network pharmacology research suggested that the anti-influenza mechanism of HQS was related to TLRs, MAPK, and other signal transduction pathways. Taken together, this study identified the possibility of the combined use of HQS and OS and demonstrated the role of HQS in modulating the gut microbiota of mice against influenza. Network pharmacology studies also suggested that the anti-influenza effect of HQS was related to TLRs, MAPK, TNF, and other signaling pathways.